Trends of cannabis use and related harms before and after legalization for recreational purpose in a developing country in Asia - Rasmon Kalayasiri; Suriyan Boonthae (BMC Public Health, 2023)
Abstract Background Thailand was the first country in Asia to legalize the use and purchase of cannabis leaves in February 2021 and the whole plant in June 2022 after the 2019 allowance for medical purposes. The study explored trends in cannabis use in Thailand before and after the recreational cannabis allowance was imposed. Methods Cannabis and other variables of substance use, cannabis use disorder, and attitude towards cannabis of the Thai population aged 18 to 65 years in 2019 (n = 5,002), 2020 (n = 5,389) and 2021 (n = 5,669) were obtained from annual surveys conducted in the last two months of each year by the Centre for Addiction Studies. The surveys were repeat cross-sectional surveys of the general population of Thailand. Repeated variables from at least two annual surveys were included for analysis using the Chi-square test and the t-test. Results The prevalence of cannabis use in the past year had increased from 2.2% in 2019 to 2.5% and 4.2% in 2020 and 2021 respectively, while those of methamphetamine, alcohol, and tobacco use had decreased. Trends in past-year drinking/eating cannabis products had increased, especially among the middle age group (40–49 years) from 2.1% (95% confidence interval (CI): 1.3, 3.1) in 2019 and 1.1% (95% CI: 0.6, 1.9) in 2020 to 3.8% (95% CI: 2.8, 5.0) in 2021. The younger population aged 18–19 had an increase in cannabis smoking from 0.9% (95% CI: 0.1, 3.3) in 2019 to 2.0% (95% CI: 0.5, 5.1) and 2.2% (95% CI: 0.7, 5.1) in 2020 and 2021 respectively. Symptoms of cannabis use disorder among cannabis users increased from 2019 to 2020 and then reversed afterwards in 2021. Thais had greater health knowledge about the benefits and harms of cannabis and had attitudes toward more harm of cannabis in 2021; however, 35.6% or a third of the sample in 2021 truly believed that cannabis was a cure for cancer, and 23.2% or one-fourth were uncertain or did not believe that cannabis was addictive. Conclusions Although most of the substances had a lower prevalence of use during the COVID-19 pandemic in Thailand, cannabis had a higher use after legalization. Thai youth had a growing trend to smoke cannabis.